Pengaruh Lingkungan Kerja terhadap Turnover yang dimediasi oleh Kepemimpinan pada PT Aniwa Jakarta - Catherine Yusine Surbakti; Heri Winoto Tj; Soegeng Wahyoedi (MES Bogor, 2025)
Employee turnover is a major challenge in human resource management, because it can impact organizational stability, productivity and cost efficiency. This research aims to analyze the influence of the work environment on employee turnover with leadership as a mediating variable at PT Aniwa Jakarta. The research method used was a quantitative approach with a purposive sampling technique, involving 65 employees from a total population of 120 company employees. The research results show that the work environment has a positive and significant influence on turnover intention, which means that less conducive work environment conditions tend to increase employees' desire to leave the company. Factors such as limited work space, lack of facility maintenance, and limited infrastructure are the main triggers for increasing turnover rates. In addition, the authoritarian leadership style at PT Aniwa contributes to employee dissatisfaction, which further strengthens their intention to leave the company.